Gross Morphological Peculiarities of Tongue in Bewick Swan (Cygnus columbianus) - Firdous AD; Mausood J; Rezzaque C. Massarat Khan; Andleeb R; Shazia N; Umar N (Zenodo, 2022)
The present study was conducted on the tongue of the Bewick Swan (Cygnus columbianus). The tongue as a prehensile organ is involved in the food intake and in ingestion. Bewick swan is often poached when they migrate to their unusual habitat. Studying of the gross morphological characters besides adding to the knowledge anatomy will also act an aid in identifying during forensic cases and other pathological conditions. The tongue of Bewick Swan consisted of apex, body with lingual prominence and the root. The tongue was attached to the lower bill by the frenulum. The tongue was long and oval shaped characterized by a prominent longitudinal median sulcus which extends up to lingual prominence. Dorsal surface of the tongue along with the lateral borders presented numerous papilla of varying sizes while as ventral surface was smooth.